Strategic planning for the development of industrial biotechnological enterprises - A. S. Glazkova; V. A. Epifanov (Путеводитель предпринимателя)
The role of biotechnology and biotechnology products in the development of the Russian economy as a whole was determined. A comprehensive model of the interconnection between the life cycles of biotechnologies and biotechnological products, as well as information systems for controlling continuous innovations in biotechnology, was developed. Strategies for the development of biotechnology was proposed.